Epidemiology and economic impact of bovine cysticercosis in the state of Espírito Santo, Brazil - Rossi, Gabriel Augusto Marques (2022)
Bovine cysticercosis (BCC) is an important disease in Brazil due to its detection in abattoirs, resulting in economic losses for cattle farmers, and a public health corcern. Besides its importance, the knowledge about BCC epidemiology and impact remains not fully described in several areas in this country, requiring more studies. Thus, this study focused on establishing BCC prevalence in the regions and municipalities of the state of Espírito Santo from 2017 to 2019, establishing the associated risk factors, and estimating the economic losses for cattle farmers. A set of 2,330 cases of BCC was detected in the 407,529 bovine inspected by Federal Inspection Service (0.57%; C.I. 95% 0.55 – 0.60%) with a higher detection of unviable cysticercus (66.14%). The beef producers lost at least US$153,000.20 due to BCC through this period. The highest risk for BCC infection occurred in Metropolitana (OR = 9.19), Litoral Sul (OR = 7.77), Caparó (OR = 7.44), and Central Sul (OR = 7.19) mesoregions, respectively. The BCC was detected in animals from 67 municipalities and its prevalence increased in areas with high human population density (OR = 1.58;; p = 0.01). In conclusion, BCC is an important disease for beef production chain in the Brazilian state of Espírito Santo and a cause of economic losses, mainly in some areas, and urgently requires the adoption of prophylactic strategies to reduce the ocurrence of this parasite.